Zakat Atau Shadaqah dan Kaitannya Dengan Pemimpin (Kajian Ayat 103 Surat At-Taubah) - Rasyad, Rasyad (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2020)
In understanding Surah al-Taubah, verse 103, especially the word shadaqah and the word khudz, the commentators are divided into two groups. First, the mufassir argues that shadagah is ordinary alms, while the second group argues that the shadagah in the verse is obligatory shadagah (zakat), because in that verse there is the word which aims to purify oneself. However, after the verse is studied with the approach of 'ulum al-Quran especially (asbab alnuzul and munasabah verse), the word shadagah is closer to the meaning of ordinary alms, not in the sense of zakat, and the al-Taubah verse 103 verse does not order the Prophet to take zakat from muzakki, but muzakkilah or people who want to give alms should give themselves (voluntarily) zakat or sadakah. Thus, based on studies from the point of view of 'ulum al-Quran, a leader is not obliged to take zakat from the people he leads.Â  Â